Concanavalin A-conjugated gold nanoparticle/silica quantum dot (AuNPs/SiQDs-Con A)-based platform as a fluorescent nanoprobe for the bioimaging of glycan-positive cancer cells. Issue 14 (17th March 2022) - Jafarzadeh, Somayeh; Bargahi, Nasrin; Shamloo, Hassan Bagherpour; Soleymani, Jafar
Abstract : The glycan receptor is a glycosylphosphatidylinositol glycoprotein that is overexpressed on the surface of various cancer cells and has been utilized for wide applications. Abstract : The glycan receptor is a glycosylphosphatidylinositol glycoprotein that is overexpressed on the surface of various cancer cells and has been utilized for wide applications. In the present work, the surface of citrate-capped gold nanoparticles (cit-AuNPs) was modified with mercaptopropionic acid (MPA) molecules to provide carboxylic groups for secondary functionalization with amine anchored-silica quantum dots (Si-NH2 QDs) to produce cit-AuNPs-MPA/Si-NH2 QDs fluorescent nanoparticles. Concanavalin A (Con A) molecules were attached through thiol–AuNP bonds to produce the final cit-AuNPs/MPA/Si-NH2 QDs/Con A smart nanoparticles. The synthesized novel cit-AuNPs/MPA/Si-NH2 QDs/Con A nanoparticles were utilized for the bioimaging of glycan-overexpressed breast cancer cells. Fluorescence microscopy and flow cytometry results revealed that the cit-AuNPs/MPA/Si-NH2 QDs/Con A NPs can be efficiently taken up by cancer cells, with differentiating ability between overexpressed cancer cells and low-expressed normal cells. The cellular viability of the cit-AuNPs/MPA/Si-NH2 QDs/Con A NPs was tested by the MTT test, proving their biocompatible nature at the 200 μg mL −1 level. In conclusion, the fabricated cit-AuNPs/MPA/Si-NH2 QDs/Con A NPs could be utilized for the bioimaging of MCF-7 cancer cells even in the clinical setting after proper in vivo validation.